Serum lactate and LDH are related with theta and gamma activities in bipolar disorder: a band-specific metabolic coupling - Kesebir, Sermin; Demirer, Rüştü Murat (Frontiers in Psychiatry, 2025)
ObjectiveBipolar disorder includes features of a biphasic energy disregulation. Lactate and LDH have been suggested as biomarkers for mitochondrial dysfunction, which has a role in its etiology. This study aims to examine the correlation between electrophysiological brain dynamics, quantified by Entropy Doubling and Ruzsa Distance derived from EEG data, and peripheral lactate and lactate dehydrogenase (LDH) levels in patients with bipolar disorder in remission.MethodsIn this study, 20 individuals diagnosed with Bipolar Disorder Type I following DSM-V criteria were consecutively assessed throughout their remission phase while attending our outpatient unit for routine evaluations. Metabolic syndrome and the usage of conventional antipsychotics serves as an exclusion criterion. We examined serum LDH and lactate levels and did EEGs. All EEG data is arranged with a sample rate of 125 Hz. The additive combinatorial entropy of the electrodes is what makes up the entropic Rusza Distance. The Hilbert-based Entropy Doubling approach was used to process the analytical signals for each EEG channel.ResultsEnergy dysregulation includes theta and gamma frequency bands, both in relation to lactate and LDH. Lactate and LDH levels in the F7 theta band were linearly correlated. A negative correlation was found between the levels of lactate and LDH levels in the O1, Fz, and Cz gamma bands.ConclusionOur findings suggest that there is a unique relationship between electrophysiological brain dynamics and mitochondrial dysfunction mediated metabolic stress in bipolar disorder.